Atomically dispersed reactive centers for electrocatalytic CO2 reduction and water splitting - Zhang, Huabin (2022)
Developing electrocatalytic energy conversion technologies for replacing the traditional energy source is highly expected to resolve the fossil fuel exhaustion and related environmental problems. Exploring stable and high-efficiency electrocatalysts is of vital importance for the promotion of these technologies. Single-atom catalysts (SACs), with atomically distributed active sites on supports, perform as emerging materials in catalysis and present promising prospects for a wide range of applications. The rationally designed near-range coordination environment, long-range electronic interaction and microenvironment of the coordination sphere cast huge influence on the reaction mechanism and related catalytic performance of SACs. In the current Review, some recent developments of atomically dispersed reactive centers for electrocatalytic CO2 reduction and water splitting are well summarized. The catalytic mechanism and the underlying structure-activity relationship are elaborated based on the recent progresses of various operando investigations. Finally, by highlighting the challenges and prospects for the development of single-atom catalysis, we hope to shed some light on the future research of SACs for the electrocatalytic energy conversion.